Energy transport in EuAl₂.₀₇(B₄O₁₀)O₀.₆ nanocrystals with two-dimensional Eu³⁺ sublattice - Kononets, N.V.; Seminko, V.V.; Maksimchuk, P.O.; Bespalova, I.I.; Malyukin, Yu.V.; Grynyov, B.V. (Functional Materials, 2017)
Energy transport processes in EuAl₂.₀₇(B₄O₁₀)O₀.₆ nanocrystals with two-dimensional arrangement of Eu³⁺ subsystem were investigated using the methods of stationary and time-resolved spectroscopy. Sufficient difference in Eu³⁺- Eu³⁺ distances inside and between (001) planes (4.58 A vis 9.28 A, respectively) leads to two-dimensional character of energy migration. Comparison of energy transport processes in aluminium borate nanocrystals with two-dimensional (EuAl₂.₀₇(B₄O₁₀)O₀.₆) and three-dimensional (EuAl₃(BO₃)₄) arrangement of Eu³⁺ ions have shown that despite higher Eu³⁺-Eu³⁺ shortest distances (5.9 A), energy migration in EuAl₃(BO₃)₄ leads to stronger quenching of Eu³⁺ luminescence.